Coulomb dynamics near equilibrium of two equal negative charges in the field of fixed two equal positive charges - Skrypnik, W. I. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
Periodic and quasiperiodic solutions of the Coulomb equation of motion of two equal negative charges in the field of twofixed and equal positive charges are found with the help of the Lyapunov center theorem.